Aging and sexual activity: gynecological, sexological and psychological aspects - Jarząbek-Bielecka, Grażyna; Sowińska-Przepiera, Elżbieta; Pawlaczyk, Michał (Menopause Review/Przegląd Menopauzalny, 2012)
Aging brings about a number of physical and psychological changes that can have an impact on sexual performance and pleasure. Sexual activity is a natural and important part of a healthy lifestyle, no matter what women’s or men’s age is. Although the amount of sexual activity generally declines with age, sexual interest and ability can remain fairly constant. While the need for and interest in sex vary widely in people, most people experience sexual desire throughout life. A diversity of complex controlling factors as well as an abundance of ways in which human sexuality is expressed remains an important methodological problem which impedes a scientific description of the phenomenon in question. In modern society many aspects of lifestyle, including physical activity, love, sex, fashion, learning and others have crossed the border set in the past. More attention needs to be paid to sexual problems of our aging patients.